Efektivitas Perebusan dan Perendaman NaCl dalam Menurunkan Toksisitas HCN pada Daun Singkong (Manihot esculanta Crantz) - Inayah, Inayah; Sahani, Wahyuni; Ahmad, Hamsir; Cahyani, Amelia (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
Cassava leaves (Manihot Esculanta Crantz) are widely used by the community as a vegetable, however they contain high levels of cyanide acid (HCN), for this reason they need to be processed properly and correctly. This research aims to determine the processing process to reduce cyanide acid (HCN) levels in cassava leaves (Manihot Esculanta Crantz). This type of research is a quasi-experiment with a Pre-Post Test Control Design design by immersing in NaCl solution using a concentration of 2% and a boiling process for 40 minutes and replication 3 times. The data obtained based on the results of observations during experiments were then presented in written and tabular form and then analyzed descriptively regarding the reduction in cyanide acid (HCN) levels in cassava leaves (Manihot Esculanta Crantz). The results of the research showed that before treatment, the HCN level was found to be 0.00156 mg/kg, whereas after treatment, namely soaking with 2% NaCl solution, the average result was 0.00725 mg/kg with a decrease of 53.5% and for boiling it was 0.00181 mg/kg with a reduction of 88.3%. The conclusion of this research is that the boiling process has a greater effect on reducing cyanide acid (HCN) levels in cassava leaves (Manihot Esculanta Crantz) compared to the soaking process with NaCl solution. It is recommended to apply cassava leaf processing using the boiling method to reduce HCN levels